Desarrollo de la ingeniería conceptual requerida para el diseño y construcción de una planta de GNL en Chira, Ghana (2019)
The principal objective of this project is to develop the conceptual engineering in order to design and build an LNG plant, located in Chirano, Ghana. The contracting enterprise wants to manage and transport 12 MMSCFD to remote locations in Ghana. The actual gasoduct does not have the desired paths that need to be used in order to transport this commodity and building a new want wont make the transportation profitable. That is why, the solution for this issue is to liquify the natural gas to be transported through tanker trucks. The conceptual engineering is needed and is the one developed through this research. First, a description of the country where the plant is going to be located is made, its oil and gas economy and the geographical implications. Followed by the initial description, the LNG general process is explained, including the pretreatment processes and the different liquefaction techniques that are developed nowadays in the industry. Second, the chromatography of the gas that needs to be treated is analyzed, in order to characterize the flow. As a consequence of this characterization and analysis, the design of the plant is done, depending on the composition that the chromatography shows (amount of methane, ethane, propane, heavier hydrocarbons and contaminants). The proper processes are selected hinged on the former characterization and the design criteria provided by the contractor enterprise. The conceptual engineering is developed in the software Aspen Hysys 8.8, where the complete processes are simulated, making special emphasis in the liquefaction process. Finally, a financial study is done in order to evaluate the viability of the development and construction of the LNG plant.